2019
DOI: 10.18295/squmj.2019.19.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use and Addiction Among Medical Students in Qassim University, Saudi Arabia

Abstract: Objectives: This study aimed to measure the prevalence of Internet use and addiction and determine its association with gender, academic performance and health among medical students. Methods: This cross-sectionalstudy was conducted between December 2017 and April 2018 at the College of Medicine, Qassim University, Buraydah, Saudi Arabia. The validated Internet Addiction Test questionnaire was distributed by simple random methods to medical students (N = 216) in the pre-clinical phase (first-, second- and thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
32
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 25 publications
(35 reference statements)
11
32
10
Order By: Relevance
“…Regarding the gender differences in internet addiction, the present study found that female medical students were severely addicted to internet more than males (71.5% of the severe internet addicts were females compared to 28.5% were males), which is consistent with ndings of Taha et al in their study (Taha et al 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the gender differences in internet addiction, the present study found that female medical students were severely addicted to internet more than males (71.5% of the severe internet addicts were females compared to 28.5% were males), which is consistent with ndings of Taha et al in their study (Taha et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the majority of our medical students (86.6%) were found at least often depressed or moody when they were o ine. This is higher than that found by Taha et al, 2019 as 60.7% of their included medical students felt at least frequently depressed when they are o ine (Taha et al 2019). These results were in line with ndings from other studies done in Korea and India (Whang et al 2003and Srijampana et al 2014).…”
Section: Discussionmentioning
confidence: 52%
“…News in 2014 surprisingly reported that people of Saudi Arabia waste their time spending 8 hours on Internet each day, However, Larson et al (2015), reported that 66.3% of people spend 0.5 to 1 hour on social media per day and few of them (32.2%) spend more than one hour per day (23). It seems that the reason for this increase in use of social media is the advent of more easy-access smart devices, creating the need for people to use them for their daily and essential tasks, speeding up communication and entertainment, and also lack of facilities such as well-equipped gyms and recreational activities near the University campus and lack of interest in the eld of study.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, the level of social media addiction among medical students has reached 12.4%. 5 Internet addiction has a negative impact on medical students, especially on their academic achievements, and physical health. 5 High social anxiety, low self-esteem and depression are also associated with social media addiction in medical students.…”
Section: Introductionmentioning
confidence: 99%
“…5 Internet addiction has a negative impact on medical students, especially on their academic achievements, and physical health. 5 High social anxiety, low self-esteem and depression are also associated with social media addiction in medical students. 6 Considering the amount of social network addiction and the negative impacts it potentially creates, researchers have started examining the risk factors of social media addiction.…”
Section: Introductionmentioning
confidence: 99%